Pain management at the orthopaedoc spine clinic located at the Chris Hani Baragwanath Academic Hospital - Maina, Anne Wanjiru (My University, 2018)
This study examined outpatient disability in chronic low back pain (cLBP), assessed whether patients received treatment, and clinicians’ prescribing habits. Methods and materials: This prospective, single-centre cross-sectional study was conducted from the 1st of July to the 31st of October 2016. An Oswestry Disability questionnaire (ODI) and medical records were surveyed in 279 participants. Results: The median ODI was 48.9%. More than 50% of patients reported ‘fairly severe’ to ‘very severe’ pain that significantly limited walking distance and ability to lift objects. In contrast, standing, sitting, travel and social life were relatively unaffected. Paracetamol was readily available 23% of the time, non-steroidal antiinflammatories 46%, and opioid-like drugs 7%. Discussion: The above average ODI and its discrepant impact on Activities of Daily Living may be due to drug shortages with patients judiciously self-dosing for selected activities. Conclusion: Pain significantly disabled participants. Essentially all drugs underwent shortages despite clinician compliance with evidence-based protocols.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine, Johannesburg 2018
Keywords: Pain Management; Low Back Pain; Outpatients